"Live It to Understand It": The Experiences of Mothers of Children With Autism Spectrum Disorder. (June 2016) - Nicholas, David B.; Zwaigenbaum, Lonnie; Ing, Stanley; MacCulloch, Radha; Roberts, Wendy; McKeever, Patricia; McMorris, Carly A.
Mothers of children with an autism spectrum disorder (ASD) variably experience challenges in their caregiving role. This ethnographic study examined the caregiving experiences of mothers of a young person with ASD (aged ≤25 years). Semistructured interviews were conducted with 85 mothers across three Canadian regions. A follow-up subsample of 10 mothers took part in participant observation sessions in the home and/or other environments within the community. Analysis yielded themes that depicted the following: redefining child and family aspirations, forging a shifted identity, and the need to "live it" to understand mothering a young person with ASD. Supports and services were perceived to be required but often insufficient to meet the needs. Findings identify a range of challenges, lessons learned, and a reconfigured sense of mothering. An emerging model of mothering a child with ASD is presented. Implications for practice, policy, and research are offered.